LUISIELLA INEXCUTATA GEN. ET SP. NOV. (PISCES, CLUPEIFORMES, DUSSUMIERIIDAE) DEL ]URASICO SUPERIOR?DE LA PROVINCIA DE CHUBUT, ARGENTINA (Ameghiniana, 2013)
The author describes Luisiella i?nexcutata nov. gen., nov. sp. from Chubut 43c25'L.S probably nearer to the Leptolepiforme sand undoubtedly a member of the Clu- pei?forrnes. Luisiella is assigned to the Duesumieriidao (Spratelloidi?nae) principally by the obsce?iice of pelvic scuta. The age Late Jurassic, is certified by paleobotanical and lithologic evidences. Lui?siella inexcutata is the most anci?ent Dussumieriidae, found up to know, and is the only representative known in South America. One can presume that the ecological condi?ti?ons cf the cenosis integrated by this fish was very different compared with the conditions prevailing in recent t.rnes in Patagonia, and points to a tropical environment during the Mesozoic.